Transportation Effects on Spatial Structure of Hungary - Erdősi, Ferenc (Discussion Papers, 1992)
On account of its geographical situation Hungary, as a meeting point of transcontinental transport, has a significant transit function and it is the place where the communication channels linking Western and Eastern Europe as well as Northern and Southern Europe converge. To make use of a technical term: Hungary is a “ferry-country”. Also because of the above mentioned endowment in comparison with the socio-economic development level of the country a high-standard railway-network has been built which porved to be an unusually strong spatial structure-shaping factor. In the present paper, the author is going to give a brief survey of the characteristic features of the interaction between the transport network and the general regional structure.